Anion exchange membrane containing long carbon fluorine chains and preparation method thereof
By introducing long oxygen-containing fluorine-containing side chains into the anion exchange membrane and using a highly stable quaternary amine salt structure, the existing membrane is easily degraded and has too high water absorption under strong alkaline conditions, and the membrane performance with high stability, flexibility and ionic conductivity is achieved.
Patent Information
- Application Number
- CN202410186100.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-20
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-02-20
AI Technical Summary
The existing poly(arylpiperidine) type anion exchange membrane is prone to degradation under strong alkaline conditions, and the water absorption and swelling rate are too high, resulting in the membrane being easily frail.
An anion exchange membrane containing long carbon fluorine chains was designed, and the alkali stability and flexibility of the membrane were improved by introducing long oxygen-containing fluorine-containing side chains and using a high-stability quaternary amine salt structure.
High stability and high flexibility under strong alkaline conditions are achieved, while ensuring the ionic conductivity of the film and avoiding the problem of water absorption and fragmentation of the film.
Smart Images

Figure CN118063742B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to anion exchange membranes, and more particularly to anion exchange membranes containing long carbon fluorine chains and their preparation methods, belonging to the field of anion exchange membrane technology. Background Technology
[0002] Hydrogen is hailed as a clean energy source that can replace petroleum energy in the future. As a result, proton exchange membrane electrolysis of water (PEMEW) has been widely developed over the past two decades. However, the widespread application of water electrolysis technology requires the use of precious metals as catalysts, which is too high in terms of sustainability and cost-effectiveness.
[0003] Therefore, as an alternative to PEMEB, anion exchange membrane fuel cells (AEMEW) are attracting increasing attention due to the potential use of inexpensive nickel metal as a catalyst. AEMEB using nickel as an electrocatalyst has been proven to have high power output and reasonable durability.
[0004] However, in the existing technology, the main chain of poly(arylpiperidine) type AEM is composed of a rigid benzene ring, and the AEM also contains N-containing hydrophilic groups, which makes the water absorption rate and swelling rate of the AEM too high. Under the condition of unavoidable water absorption and swelling rate, the excessive rigidity can easily lead to the membrane absorbing water and breaking.
[0005] Secondly, although the base stability of PAP is improved compared with other types of AEM, it is still easily degraded under strongly alkaline conditions, such as the ring-opening Hoffmann elimination reaction. The ion loss of piperidine cations is partly due to the conformational failure of the piperidine ring directly attached to the rigid PAP backbone. In addition, when the ring is relaxed, the cation loss will increase further when it is further restricted by the spirocyclic arrangement of ASU cations. To address these issues, a long carbon fluorine chain anion exchange membrane and its preparation method were designed. Summary of the Invention
[0006] The main objective of this invention is to provide an anion exchange membrane containing long carbon fluorine chains and its preparation method.
[0007] The objective of this invention can be achieved by adopting the following technical solution:
[0008] An anion exchange membrane containing a long carbon fluorine chain, wherein the polymer comprises two structural units as shown in the following formula;
[0009]
[0010] In Equation 1:
[0011] n is the degree of polymerization, and m represents the length of the alkane chain, which is an integer between 2 and 9.
[0012] k is an integer between 1 and 9;
[0013] In Equation 2:
[0014] n represents the degree of aggregation, and k represents the number of —CF2— which is an integer between 0 and 9.
[0015] Preferably, in Formula 1:
[0016] R1 represents One or more of them.
[0017] Preferably, in Equations 1 and 2:
[0018] Ar aromatic hydrocarbons include one or more of the following:
[0019]
[0020] In the above formula, R2, R3, and R4 are any one of hydrogen, halogroup, alkyl, alkenyl, alkynyl, or aryl;
[0021] Furthermore, the alkyl, alkenyl, alkynyl, or aryl groups may be optionally substituted with one or more halogenated groups.
[0022] Preferably, in Equations 1 and 2:
[0023] One or more of the R2 and R3 structures:
[0024]
[0025] In the above formula, P is an integer between 3 and 12, and R7 and R8 are H or C1-C. 10 Any one of the alkanes.
[0026] Preferably, in the formula, Ar is an aromatic hydrocarbon a, which is an integer between 1 and 6, and R5 and R6 are any one of hydrogen, halogroup, alkyl, alkenyl, alkynyl or aryl;
[0027] Furthermore, the alkyl, alkenyl, alkynyl, or aryl groups may be substituted with one or more halogenated groups;
[0028] Ar1 and Ar2 are each independently selected from one or more of the following:
[0029]
[0030] In Equation 1, R is selected from one of the following structures:
[0031]
[0032] X- represents Br-, I-, Cl-, OH-, HCO3-, and CO3-. 2-
[0033] In the formula, R9 represents any one of H or C1-C10 alkanes.
[0034] The catalysts are trifluoromethanesulfonic acid and trifluoroacetic acid.
[0035] The solvent is one or more of DCM, chloroform, and 1,2-dichloroethane.
[0036] In Equation 2, R100 is selected from one of the following structures:
[0037]
[0038] X- represents Br-, I-, Cl-, OH-, HCO3-, and CO3-. 2- ;
[0039] R1 and R2 represent H, C1-C10 alkanes;
[0040] The catalysts are trifluoromethanesulfonic acid and trifluoroacetic acid;
[0041] The solvent is one or more of DCM, chloroform, and 1,2-dichloroethane.
[0042] A method for preparing anion exchange membrane containing long carbon fluorine chains includes the following steps:
[0043] Step 1: Synthesize the ketone monomer to obtain a light brown crystalline product;
[0044] Step 2: Dissolve the light brown crystalline product and p-terphenyl in DCM, cool to sub-zero temperature in an ice bath, add TFSA dropwise, and polymerize under ice bath conditions for 2 hours to 12 days after the addition is complete.
[0045] After the reaction was complete, DMSO was added to quench and dissolve the polymer. The solid was then immersed in ice water to obtain a white solid, which was repeatedly washed with deionized water and then vacuum dried.
[0046] Step 3: Dissolve the dried white solid from the previous step in a polar solvent, quickly add iodomethane solution and stir for more than 12 hours, dissolve the precipitate in ethyl acetate, filter to obtain a yellow solid, wash with distilled water and dry;
[0047] Step 4: After washing with distilled water and filtering, a yellow powdery polymer is obtained. The obtained polymer is dried, then centrifuged after being treated with a polar solvent, cast onto a plate, dried to form a film, dried under vacuum, and then subjected to hydroxide ion exchange in a sodium hydroxide solution to obtain an anion exchange membrane in the form of hydroxide ions.
[0048] Preferably, in step one, the ketone monomer 2,2,2-trifluoromethyl-1-(1-methyl-4-piperidine) ethyl ketone is synthesized. 1-methyl-4-piperidinecarboxylic acid (143 g, 1 mol, 1 eq) is dissolved in toluene (400 mL) in a 2500 mL three-necked flask. TFAA (trifluoroacetic anhydride, 780 mL, 5.6 mol, 5.58 eq) is slowly added with stirring in an ice bath. After cooling to 0 °C, pyridine (650 mL, 8 mol, 8 eq) is added dropwise. After the addition is complete, the temperature is raised to 50 °C, and the reaction is carried out under nitrogen for 48 h. Then, the temperature is lowered to 0 °C, 1430 mL of deionized water is added dropwise, and the temperature is raised to 45 °C for 2 h.
[0049] After the reaction was completed, the layers were allowed to stand and separate. The organic layer was extracted with ethyl acetate (4 x 1250 mL). The organic phase was washed successively with deionized water, saturated sodium carbonate, and saturated sodium chloride solution, and then dried with anhydrous sodium sulfate. The solvent was then evaporated, and the product was separated by column chromatography to obtain a light brown crystalline product (130 g, yield 30%), which was used to synthesize the molecular structure in Formula 2.
[0050] Preferably, in step one, the ketone monomer 8-chloro-1,1,1,2,2,3,3-heptafluorooctan-4-one is synthesized. In a 5000 mL three-necked flask, toluene (400 mL) and 5-chlorobutyric acid (136 g, 1 mol, 1 eq) are slowly added under stirring in an ice bath, followed by perfluorobutyric anhydride (1370 mL, 5.6 mol, 5.58 eq). After cooling to 0 °C, pyridine (650 mL, 8 mol, 8 eq) is added dropwise. After the addition is complete, the temperature is raised to 50 °C, and the reaction is carried out under nitrogen for 48 h. Then, the temperature is lowered to 0 °C, 1430 mL of deionized water is added dropwise, and the temperature is raised to 45 °C for 2 h.
[0051] After the reaction was completed, the layers were allowed to stand and separate. The organic layer was extracted with ethyl acetate (4 x 1250 mL). The organic phase was washed successively with deionized water, saturated sodium carbonate, and saturated sodium chloride solution, and then dried with anhydrous sodium sulfate.
[0052] The solvent was then evaporated, and the product was separated by chromatographic column chromatography to obtain a light brown crystalline product (57.6 g, yield 20%).
[0053] Preferably, in step two, the light brown crystals (28.8 g, 1.2 eq) and biphenyl (15.4 g, 1 eq) from the previous step are dissolved in DCM (100 mL), cooled to 0 °C in an ice bath, and TFSA (79.6 mL, 9 eq) is added dropwise. After the addition is complete, polymerization is carried out under ice bath conditions for 2 h-12 d.
[0054] After the reaction was complete, DMSO was added to quench and dissolve the polymer. The solid was then immersed in ice water to obtain a white solid. After rinsing several times with deionized water, the solid was dried under vacuum at 80°C for 12 hours.
[0055] Preferably, in step three, the white solid dried in the previous step is dissolved in a polar solvent (NMP, DMF, DMSO, DMAc), a trimethylamine solution is quickly added and stirred for more than 12 hours, the precipitate is dissolved in ethyl acetate and filtered to obtain a yellow solid, which is then washed with distilled water and dried.
[0056] Preferably, in step four, the polymer is washed with distilled water and filtered to obtain a yellow powder. The obtained polymer is then vacuum dried at 80°C for 24 hours, dissolved in a polar solvent (one or more of NMP, DMF, DMSO, and DMAc), centrifuged, cast onto a glass or stainless steel plate, and dried at 60–100°C for 5–24 hours to form a film. The film is then vacuum dried at 80–150°C for 5–24 hours, with a thickness between 10 and 100 μm. The film is then subjected to hydroxide ion exchange in a 1M sodium hydroxide solution at 80°C to obtain an anion exchange membrane in the form of hydroxide ions.
[0057] Beneficial technical effects of the present invention:
[0058] This invention provides an anion exchange membrane containing long carbon fluorine chains and its preparation method. This invention introduces long oxygen-containing carbon fluorine side chains and uses a quaternary ammonium salt structure with high stability, which improves alkali stability while ensuring ionic conductivity.
[0059] The introduction of alkane side chains, oxygen-containing fluorocarbon side chains, and sulfur-containing fluorocarbon chain chains increases flexibility, making it more soluble in organic solutions. Attached Figure Description
[0060] Figure 1 This is the product of Structural Embodiment 1 of the present invention. 1 HNMR.
[0061] Figure 2 This is the product of Structural Embodiment 1 of Formula 2 of the present invention. 1 HNMR. Detailed Implementation
[0062] To enable those skilled in the art to understand the technical solution of the present invention more clearly, the present invention will be further described in detail below with reference to the embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto.
[0063] Formula 1 Molecular Formula
[0064]
[0065] The following preparation method is adopted;
[0066] Example 1
[0067] Synthetic ketone monomers:
[0068] 8-chloro-1,1,1,2,2,3,3-heptafluorooctan-4-one was added to a 5000 mL three-necked flask with toluene (400 mL) and 5-chlorobutyric acid (136 g, 1 mol, 1 eq). Perfluorobutyric anhydride (1370 mL, 5.6 mol, 5.58 eq) was slowly added with stirring in an ice bath. After cooling to 0 °C, pyridine (650 mL, 8 mol, 8 eq) was added dropwise. After the addition was complete, the temperature was raised to 50 °C and the reaction was carried out under nitrogen for 48 h. Then, the temperature was lowered to 0 °C and 1430 mL of deionized water was added dropwise. The temperature was then raised to 45 °C and the reaction was carried out for 2 h.
[0069] After the reaction was completed, the layers were allowed to stand and separate. The organic layer was extracted with ethyl acetate (4 x 1250 mL). The organic phase was washed successively with deionized water, saturated sodium carbonate, and saturated sodium chloride solution, and then dried with anhydrous sodium sulfate. The solvent was then evaporated, and the product was separated by chromatographic column chromatography to obtain a light brown crystalline product (57.6 g, yield 20%).
[0070] Polymer synthesis: The light brown crystals (28.8 g, 1.2 eq) and biphenyl (15.4 g, 1 eq) from the previous step were dissolved in DCM (100 mL), cooled to 0 °C in an ice bath, and TFSA (79.6 mL, 9 eq) was added dropwise. After the addition was complete, polymerization was carried out under ice bath conditions for 2 h–12 d. After the reaction was complete, DMSO was added to quench and dissolve the polymer. The solid was then precipitated in ice water to obtain a white solid, which was repeatedly washed several times with deionized water and then dried under vacuum at 80 °C for 12 h.
[0071] Synthesis of quaternary ammonium salt: Dissolve the dried white solid from the previous step in a polar solvent (NMP, DMF, DMSO, DMAc, etc.), quickly add trimethylamine solution and stir for more than 12 hours, dissolve the precipitate in ethyl acetate, filter to obtain a yellow solid, wash with distilled water and dry.
[0072] After washing with distilled water and filtering, a yellow powdery polymer was obtained. The polymer was then vacuum dried at 80°C for 24 hours, dissolved in a polar solvent (NMP, DMF, DMSO, DMAc or one or more), centrifuged, and cast onto a glass or stainless steel plate. The film was then dried at 60–100°C for 5–24 hours to form a membrane, and then vacuum dried at 80–150°C for 5–24 hours. The membrane thickness was between 10 and 100 μm. The membrane was then subjected to hydroxide ion exchange in a 1M sodium hydroxide solution at 80°C to obtain an anion exchange membrane in the form of hydroxide ions.
[0073] The synthesis reaction equation is shown below.
[0074]
[0075] Example 2
[0076] Synthesis of ketone monomer: In a dry 500 mL reaction flask, 17.0 g (0.12 mol) of white solid phosphorus pentoxide powder and 10.0 g of activated carbon pre-activated by drying at 100-130 °C were added. 150 mL of toluene solvent dried with anhydrous sodium sulfate was added. After mixing and dispersing evenly under mechanical stirring, 53.64 g (0.298 mol) of 2,2-difluoro-2-(trifluoromethoxy)acetic acid was slowly added dropwise, and the temperature was slowly raised to reflux. The reaction was carried out for 1.5 h. The fraction obtained at 150 °C was distilled under normal pressure. The obtained fraction was then further distilled through a distillation column to obtain 19.8 g of reagent-grade product 2,2-difluoro-2-(trifluoromethoxy)acetic anhydride at 150 °C-165 °C, with a yield of 59.4%. Then, 6-chloro-1,1-difluoro-1-(trifluoromethoxy)hexan-2-one was synthesized in the same manner as in step 1 of Example 1.
[0077] The other steps are the same as in Example 1;
[0078] The synthesis equation is shown below;
[0079]
[0080] Example 3
[0081] The ketone monomer 6-chloro-1,1-difluoro-1-((trifluoromethyl)thio)hexan-2-one was synthesized in the same manner as in Example 2.
[0082] The other steps are the same as in Example 1 for synthesizing anion exchange membranes.
[0083] The synthesis equation is shown below;
[0084]
[0085] Example 4
[0086] Same as in Example 1, synthesize ketone monomers 6-chloro-1,1-difluoro-1-(trifluoromethoxy)hexan-2-one and 8-chloro-1,1,1,2,2,3,3-heptafluorooctan-4-one.
[0087] In the same manner as in Example 1, the amounts of the ketone monomers 6-chloro-1,1-difluoro-1-(trifluoromethoxy)hexan-2-one and 8-chloro-1,1,1,2,2,3,3-heptafluorooctan-4-one were 1:1.
[0088] Synthesize the following anion exchange membrane.
[0089]
[0090] Example 5
[0091] The same anion exchange membrane as in Example 1 was synthesized as shown below.
[0092]
[0093] Comparative Example 1
[0094] The ketone monomer 6-chloro-1,1,1-trifluorohexan-2-one was synthesized by slowly adding trifluoroacetic anhydride (778 mL, 5.6 mol, 5.58 eq) to toluene (400 mL) and 5-chlorobutyric acid (13.6 g, 1 mol, 1 eq) with stirring in an ice bath. After cooling to 0 °C, pyridine (650 mL, 8 mol, 8 eq) was added dropwise. After the addition was complete, the temperature was raised to 50 °C, and the reaction was carried out under nitrogen for 48 h. Then, the temperature was lowered to 0 °C, 1430 mL of deionized water was added dropwise, and the temperature was raised to 45 °C for 2 h. After the reaction was completed, the layers were allowed to separate. The organic layer was extracted with ethyl acetate (4 x 1250 mL). The organic phase was washed successively with deionized water, saturated sodium carbonate, and saturated sodium chloride solution, and then dried with anhydrous sodium sulfate. The solvent was then evaporated, and the product was separated by column chromatography to obtain a light brown crystalline product (113 g, 60% yield).
[0095] The other steps are the same as in Example 1;
[0096] The synthesis reaction equation is as follows;
[0097]
[0098] Comparative Example 2
[0099] Synthesis of poly(arylpiperidine): Biphenyl (15.4 g, 0.1 mol, 1 eq) and N-methyl-4-piperidinone (15.9 mL, 0.13 mol, 1 eq) were added to a 250 mL three-necked flask and dissolved in 60 mL of dichloromethane.
[0100] Polymerization was initiated by adding trifluoromethanesulfonic acid (79.6 mL, 0.9 mol, 9 eq) under ice bath conditions. After the reaction was complete, the solid was poured into methanol to precipitate a white solid, which was then washed with deionized water and dried under vacuum at 80 °C for 12 h.
[0101] Synthesis of quaternary ammonium salt: The white solid dried in the previous step was dissolved in a polar solvent (NMP, DMF, DMSO, DMAc, etc.), and iodomethane solution was quickly added and stirred for more than 12 hours. The precipitate was dissolved in ethyl acetate and filtered to obtain a yellow solid. The solid was washed with distilled water and dried under vacuum at 80°C for 12 hours to obtain a light yellow solid.
[0102] The synthesis reaction equation is as follows;
[0103]
[0104]
[0105] The testing method is as follows:
[0106] Alkali stability: Change in polymer conductivity before and after immersion in 5M sodium hydroxide solution at 80℃ for 1000 hours.
[0107] Elongation at break: The test method refers to the mechanical property test method of proton exchange membrane GB / T 20042.3-2022.
[0108] Conductivity: The OH- ion conductivity of the fully wet anion exchange membrane in pure water was measured using the four-electrode AC impedance method. The specific test parameters are as follows: A membrane material with an area of 5 mm × 10 mm and a thickness of 40 μm was used. AC impedance testing was conducted using a Chenhua (CHI760E) electrochemical workstation within the frequency range of 1 Hz to 1000 K Hz. The ion conductivity was calculated by fitting the curve. The test temperature was 25℃.
[0109] As can be seen from the test results in the table above, according to the technical solution of this invention:
[0110] Based on the test results of Examples 1, 2, and 3 and Comparative Example 1, it was found that the membrane stability manufactured by this design scheme was improved by 10.24% to 14.57%.
[0111] Based on the test results of Example 1 and Comparative Example 1, the polymer manufactured by this design scheme has improved flexibility by 79.36% to 133.49%.
[0112] Based on the test results of Example 1 and Comparative Example 1, it was found that the ionic conductivity of the 80℃ membrane manufactured by this design scheme was increased by 16.42%.
[0113] The test results show that the membrane manufactured by this design improves the flexibility while ensuring alkali stability and membrane ionic conductivity.
[0114] Formula 2 Molecular Formula
[0115]
[0116] The following preparation method is adopted;
[0117] Example 1
[0118] The ketone monomer 2,2,2-trifluoromethyl-1-(1-methyl-4-piperidine)ethyl ketone was synthesized. 1-Methyl-4-piperidinecarboxylic acid (143 g, 1 mol, 1 eq) was dissolved in toluene (400 mL) in a 2500 mL three-necked flask. TFAA (trifluoroacetic anhydride, 780 mL, 5.6 mol, 5.58 eq) was slowly added with stirring in an ice bath. After cooling to 0 °C, pyridine (650 mL, 8 mol, 8 eq) was added dropwise. After the addition was complete, the temperature was raised to 50 °C, and the reaction was carried out under nitrogen for 48 h. Then, the temperature was lowered to 0 °C, and 1430 mL of deionized water was added dropwise. The reaction was then raised to 45 °C and carried out for 2 h. After the reaction was completed, the layers were allowed to separate. The organic layer was extracted with ethyl acetate (4 x 1250 mL). The organic phase was washed successively with deionized water, saturated sodium carbonate, and saturated sodium chloride solution, and then dried over anhydrous sodium sulfate. The solvent was then evaporated, and the product was separated by column chromatography to obtain a light brown crystalline product (130 g, 30% yield).
[0119] Polymer synthesis: The light brown crystals (22 g, 1.2 eq) and p-terphenyl (23 g, 1 eq) from the previous step were dissolved in DCM (60 mL), cooled to 0 °C in an ice bath, and TFSA (79.6 mL, 9 eq) was added dropwise. After the addition was complete, polymerization was carried out under ice bath conditions for 2 h–12 d. After the reaction was complete, DMSO was added to quench and dissolve the polymer. The solid was then precipitated in ice water to obtain a white solid, which was repeatedly washed several times with deionized water and then dried under vacuum at 80 °C for 12 h.
[0120] Fully synthesized quaternary ammonium salt: Dissolve the dried white solid from the previous step in a polar solvent (NMP, DMF, DMSO, DMAc, etc.), quickly add iodomethane solution and stir for more than 12 hours, dissolve the precipitate in ethyl acetate, filter to obtain a yellow solid, wash with distilled water and dry.
[0121] After washing with distilled water and filtering, a yellow powdery polymer was obtained. The polymer was then vacuum dried at 80°C for 24 hours, dissolved in a polar solvent (NMP, DMF, DMSO, DMAc or one or more), centrifuged, and cast onto a glass or stainless steel plate. The film was then dried at 60–100°C for 5–24 hours to form a membrane, and then vacuum dried at 80–150°C for 5–24 hours. The membrane thickness was between 10 and 100 μm. The membrane was then subjected to hydroxide ion exchange in a 1M sodium hydroxide solution at 80°C to obtain an anion exchange membrane in the form of hydroxide ions.
[0122] The synthesis reaction equation is shown below.
[0123]
[0124] Example 2
[0125] The ketone monomer 2,2,2-trifluoromethyl-1-(1-methyl-4-piperidine)ethyl ketone was synthesized in the same manner as in Example 1;
[0126] Polymer synthesis: The ketone monomer (23.4 g, 0.12 mmol, 1.2 eq) and m-terphenyl (23 g, 0.1 mol, 1 eq) from the previous step were dissolved in DCM (60 mL), cooled to 0 °C in an ice bath, and TFSA (79.6 mL, 0.9 mol, 9 eq) was added dropwise. After the addition was complete, polymerization was carried out under ice bath conditions for 2 h–12 d. After the reaction was complete, DMSO was added to quench and dissolve the polymer, which was then precipitated in ice water to obtain a white solid. The solid was repeatedly washed with deionized water several times and then dried under vacuum at 80 °C for 12 h.
[0127] The other steps are the same as in Example 1.
[0128] The synthesis equation is shown below;
[0129]
[0130] Example 3
[0131] The ketone monomer 2,2,2-trifluoromethyl-1-(1-methyl-4-piperidine)ethyl ketone was synthesized in the same manner as in Example 1;
[0132] Polymer synthesis: The ketone monomer (23.4 g, 0.12 mmol, 1.2 eq) and biphenyl (15.4 g, 0.1 mol, 1 eq) from the previous step were dissolved in DCM (60 mL), cooled to 0 °C in an ice bath, and TFSA (79.6 mL, 0.9 mol, 9 eq) was added dropwise. After the addition was complete, polymerization was carried out under ice bath conditions for 2 h–12 d. After the reaction was complete, DMSO was added to quench and dissolve the polymer, which was then precipitated in ice water to obtain a white solid. The solid was repeatedly washed with deionized water several times and then dried under vacuum at 80 °C for 12 h.
[0133] The other steps are the same as in Example 1;
[0134] The synthesis equation is shown below;
[0135]
[0136] Example 4
[0137] The ketone monomer 2,2,3,3,3-pentafluoro-1-(1-methylpiperidin-4-yl)propan-1-one was synthesized in the same manner as in Example 1.
[0138] Polymer synthesis: The ketone monomer (29.4 g, 0.12 mmol, 1.2 eq) and p-terphenyl (23 g, 0.1 mol, 1 eq) from the previous step were dissolved in DCM (60 mL), cooled to 0 °C in an ice bath, and TFSA (79.6 mL, 0.9 mol, 9 eq) was added dropwise. After the addition was complete, polymerization was carried out under ice bath conditions for 2 h–12 d. After the reaction was complete, DMSO was added to quench and dissolve the polymer, which was then precipitated in ice water to obtain a white solid. The solid was repeatedly washed several times with deionized water and then dried under vacuum at 80 °C for 12 h.
[0139] The other steps are the same as in Example 1.
[0140] The synthesis equation is shown below.
[0141]
[0142] Comparative Example 1
[0143] At room temperature, first dissolve 23 g (0.1 mol) of terphenyl and 15.9 mL (0.13 mol) of N-methyl-4-piperidinone in dichloromethane (60 mL), stir until homogeneous, and control the solution concentration at 46 wt%.
[0144] The other steps are the same as in Example 1.
[0145] The synthesis reaction equation is as follows:
[0146]
[0147] Comparative Example 2
[0148] At room temperature, firstly, 19.56 g (0.085 mol), trifluoroacetophenone (2.61 g, 0.015 mol), and N-methyl-4-piperidinone (15.9 mL, 0.13 mol) were dissolved in dichloromethane (60 mL) and stirred until homogeneous, with the solution concentration controlled at 46 wt%.
[0149] The other steps are the same as in Example 1.
[0150] The synthesis reaction equation is as follows:
[0151]
[0152]
[0153] The testing method is as follows:
[0154] Alkali stability: Change in polymer conductivity before and after immersion in 5M sodium hydroxide solution at 90℃ for 20 days.
[0155] Number-average molecular weight and weight-average molecular weight were determined by GPC with DMSO as the mobile phase.
[0156] Conductivity: The OH- ion conductivity of the fully wet anion exchange membrane in pure water was measured using the four-electrode AC impedance method. The specific test parameters are as follows: A membrane material with an area of 5 mm × 10 mm and a thickness of 40 μm was used. AC impedance testing was conducted using a Chenhua (CHI760E) electrochemical workstation within the frequency range of 1 Hz to 1000 K Hz. The ion conductivity was calculated by fitting the curve. The test temperature was 25℃.
[0157] As can be seen from the test results in the table above, according to the technical solution of this invention:
[0158] Based on the test results of Examples 1 and 3 and Comparative Example 2, it was found that the ionic conductivity of the membrane manufactured by this design scheme was increased by 12.86%.
[0159] Based on the test results of Example 1 and Comparative Example 1, it was found that the weight-average molecular weight of the polymer manufactured by this design scheme was increased by 42%.
[0160] Based on the test results of Example 1 and Comparative Example 1, it can be concluded that the membrane manufactured by this design has improved ion stability by 300%.
[0161] The above description is merely a further embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope disclosed in the present invention, based on the technical solution and concept of the present invention, shall fall within the scope of protection of the present invention.
Claims
1. An anion exchange membrane containing long carbon fluorine chains, characterized in that: The anion exchange membrane is made of a polymer including one of the two structural units of Formula 1 and Formula 2: ; ; Where: n is the degree of polymerization; m represents the length of the alkane chain, which is an integer between 2 and 9; R1 stands for One or more of, k is an integer between 1 and 9; Ar aromatic hydrocarbons include one or more of the following; ; R2 and R3 are one or more of the following structures: ; p is an integer between 3 and 12, R7 and R8 are H or C1-C 10 Any of the alkanes, X - represent One of; R4 is any one of hydrogen, halo, alkyl, alkenyl, alkynyl and aryl; and one or more of the alkyl, alkenyl, alkynyl and aryl is substituted by a halo; a is an integer between 1 and 6, R5 and R6 are any one of hydrogen, halo, alkyl, alkenyl, alkynyl and aryl; and one or more of the alkyl, alkenyl, alkynyl and aryl is substituted with a halo; Ar1 and Ar2 are each independently selected from one or more of the following: ; R is selected from one of the following structures: ; R9 represents H, C1-C 10 Any alkane; X - represent One of; In formula 2, k represents the number of —CF2— and is an integer between 1 and 9; R 100 Select one of the following structures: ; R 10 , R 11 , R 12 , R 13 Represents H, C1-C 10 Alkanes; X - represent One of them.
2. A method for preparing an anion exchange membrane containing long carbon fluoride chains as claimed in claim 1, characterized in that: The steps include: Step 1: synthesizing ketone monomer to obtain a light brown crystalline product; Step 2: Dissolve the light brown crystalline product and p-terphenyl in DCM, cool to sub-zero temperature in an ice bath, add TFSA dropwise, and polymerize in an ice bath for 2h-12d after the addition is complete; After the reaction is completed, DMSO is added to quench and dissolve the polymer, and then the solid is immersed in ice water to obtain a white solid, which is repeatedly rinsed with deionized water several times and then dried in vacuum; Step 3: Dissolve the dried white solid in the previous step with a polar solvent, quickly add iodomethane solution and stir for more than 12 hours, dissolve the precipitate with ethyl acetate, filter to obtain a yellow solid, wash with distilled water and dry; Step 4: After washing with distilled water, filter to obtain a yellow powdery polymer, dry the obtained polymer, then centrifuge it after removing a polar solvent, cast it on a plate, dry it to form a film, dry it under vacuum, and exchange the membrane with hydroxide in a sodium hydroxide solution environment to obtain an anion exchange membrane in the form of hydroxide.
3. The method for preparing a long carbon-fluorine chain anion exchange membrane according to claim 2, characterized in that: Step 1: To synthesize the ketone monomer 2,2,2-trifluoromethyl-1-(1-methyl-4-piperidinyl)ethanone, dissolve 143 g of 1-methyl-4-piperidinylcarboxylic acid in 400 mL of toluene in a 2500 mL three-necked flask, slowly add 780 mL of trifluoroacetic anhydride TFAA under stirring in an ice bath, cool to 0°C, then drop 650 mL of pyridine, and after the dropwise addition, raise the temperature to 50°C, react under nitrogen for 48 hours, then cool to 0°C, drop 1430 mL of deionized water, raise the temperature to 45°C, and react for 2 hours; After the reaction was completed, the layers were separated and the organic layer was extracted with 4*1250mL of ethyl acetate. The organic phase was washed with deionized water, saturated sodium carbonate and saturated sodium chloride solution in sequence, and then dried with anhydrous sodium sulfate. The solvent was then evaporated and separated with a chromatographic column to obtain 130g of a light brown crystalline product with a yield of 30%, which was used to synthesize the molecular structure in Formula 2.
4. The method for preparing a long carbon-fluorine chain anion exchange membrane according to claim 2, characterized in that: In step 1, the ketone monomer 8-chloro-1,1,1,2,2,3,3-heptafluorooctan-4-one was specifically synthesized by adding 400 mL of toluene and 136 g of 5-chlorobutyric acid into a 5000 mL three-necked flask, and slowly adding 1370 mL of perfluorobutyric anhydride under stirring in an ice bath, cooling to 0°C and then dropping 650 mL of pyridine. After the dropping was completed, the temperature was raised to 50°C, and the reaction was carried out under nitrogen for 48 hours, and then the temperature was lowered to 0°C, 1430 mL of deionized water was added dropwise, and the temperature was raised to 45°C for reaction for 2 hours; After the reaction was completed, the layers were separated and the organic layer was extracted with 4*1250mL ethyl acetate. The organic phase was washed with deionized water, saturated sodium carbonate, and saturated sodium chloride solution in sequence, and then dried with anhydrous sodium sulfate. The solvent was then evaporated and the product was separated by column chromatography to obtain 57.6 g of a light brown crystalline product with a yield of 20%.
5. The method for preparing a long carbon-fluorine chain anion exchange membrane according to claim 2, characterized in that: Step 2: Dissolve 28.8 g of the light brown crystalline product and 15.4 g of biphenyl in 100 mL of DCM, cool to 0°C with an ice bath, and drop 79.6 mL of TFSA. After the dropwise addition is complete, polymerize for 2 h to 12 d under ice bath conditions; After the reaction was completed, DMSO was added to quench and dissolve the polymer, and then the solid was immersed in ice water to obtain a white solid. The solid was repeatedly rinsed with deionized water for several times and then dried in a vacuum at 80° C. for 12 h.
Citation Information
Patent Citations
Poly (4-aryl) piperidine polymer, preparation method and anion exchange membrane prepared from poly (4-aryl) piperidine polymer
CN117700657A